2000
DOI: 10.1056/nejm200004203421602
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of a High-Fiber Cereal Supplement on the Recurrence of Colorectal Adenomas

Abstract: As used in this study, a dietary supplement of wheat-bran fiber does not protect against recurrent colorectal adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
339
6
18

Year Published

2002
2002
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 727 publications
(382 citation statements)
references
References 21 publications
10
339
6
18
Order By: Relevance
“…The results of this study and two recently published trials of increased fibre intake in people with colorectal adenomas (Alberts et al, 2000;Bonithon-Kopp et al, 2000), however, suggest that increasing cereal fibre intake does not confer any immediate survival advantage.…”
Section: Discussioncontrasting
confidence: 73%
“…The results of this study and two recently published trials of increased fibre intake in people with colorectal adenomas (Alberts et al, 2000;Bonithon-Kopp et al, 2000), however, suggest that increasing cereal fibre intake does not confer any immediate survival advantage.…”
Section: Discussioncontrasting
confidence: 73%
“…Indeed, we found no evidence that a high intake of fruit or vegetables is associated with a reduced risk of colorectal cancer death. Further, results from randomised controlled trials have not shown that a diet low in fat and high in fibre and fruit and vegetables can reduce the recurrence of colorectal adenomas (Alberts et al, 2000;BonithonKopp et al, 2000;Schatzkin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients that have had colorectal adenomas, recognized predictors of subsequent lesions include age, adenoma size, histology and multiplicity of the lesions at detection 1 . Depending on the age of the population, between 20 and 50% of those patients with adenomas will recur within a 3-5 year period, with 10-20% of recurrent lesions possessing clinically advanced features (larger size, villous histology, and/or high-grade dysplasia) [2][3][4][5][6] . The current recommendation for patients presenting with small polyps (less than 1 cm) is to have a followup colonoscopy 5-10 years after the initial procedure 1 .…”
Section: Introductionmentioning
confidence: 99%